Insularité et mobilités : un observatoire méditerranéen, xvie‑xviiie siècle - Mathieu Grenet; Pauline Mailloux (Diasporas: Circulations, Migrations, Histoire)
This article takes a fresh look at islands from an historical perspective. It aims to study them through the lens of mobilities, which enables us to consider islands within the context of more global dynamics of which they are a part. The Mediterranean sea and its islands in the modern period are here used as a vantage point to investigate this question, and hence take a step back from what is perhaps a more common monographic approach.